Creative clusters and place-making: analysing the quality of place in Soho and Beyoglu - Durmaz, S. Bahar (2012)
During the last decade creativity has become one of the buzz concepts of urban practice and research, and new concepts such as the creative city, creative economy, the creative class, creative industries and creative clusters have emerged (Florida, 2002; Landry, 2000). There are studies in economics and cultural geography, sociology and, to some extent in urban planning, exploring the creative city phenomenon. To date, however, there have only been a limited number of studies on understanding the dynamics and factors of the spatial conditions of the creativity debate in the discipline of urban design. The growing body of literature in these disciplines emphasises the need to identify and define the preferences and tendencies of creative industries, and also clustering activities.